2008
DOI: 10.1007/s11627-008-9164-8
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of strawberry tree (Arbutus unedo L.) from adult plants

Abstract: Arbutus unedo L. is a species of strawberry tree, widely represented in the Mediterranean climates of southern Europe. Fruits are used to make jellies and a spirit called "medronheira." Shoot apices and nodal segments from epicormic and coppiced shoots of adult plants were used for plant propagation. Shoot apices from epicormic shoots, which were developed in a growth chamber, showed higher rates of in vitro establishment. The results also indicated that shoot apices are more effective for plant establishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 26 publications
3
24
0
3
Order By: Relevance
“…Similar results have been reported for other woody species such as Eucalyptus nitens Deane &. Maiden (Gomes and Canhoto 2003) and Arbutus unedo L. (Gomes and Canhoto 2009). In the latter study, the authors suggested higher production of exudates from nodal explants or the presence in apical explants of leaf primordia which produce plant growth regulators that promote cell division and retard senescence as the possible causes of this behaviour.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results have been reported for other woody species such as Eucalyptus nitens Deane &. Maiden (Gomes and Canhoto 2003) and Arbutus unedo L. (Gomes and Canhoto 2009). In the latter study, the authors suggested higher production of exudates from nodal explants or the presence in apical explants of leaf primordia which produce plant growth regulators that promote cell division and retard senescence as the possible causes of this behaviour.…”
Section: Discussionsupporting
confidence: 88%
“…It appears that this material was sufficiently reinvigorated to provide reactive explants. Rejuvenation by forced flushing of branch segments has been described for several species (Vieitez et al 1994;Gomes and Canhoto 2009;Vieitez et al 2009). The results showed that for culture initiation, apical explants were more reactive than nodal explants.…”
Section: Discussionmentioning
confidence: 99%
“…Resultados semelhantes ao encontrado no presente trabalho foram reportados por PARK et al (2008), que observaram enraizamento de brotos de Salix pseudolasiogyne em meio de cultura WPM, na ausência de reguladores de crescimento. Em Arbus unedo L., os brotos também foram capazes de enraizar em todas as condições testadas, até mesmo na ausência de auxinas; entretanto, altas frequências de indução de raízes (entre 76,7 e 93,3%) foram alcançadas com a adição de 25,0μM de AIB no meio de enraizamento por seis dias (GOMES & CANHOTO, 2009). CARVALHO et al (2005) também verificaram que o maior número de brotações enraizadas de Bixa orellana L. ocorreu no meio ½ MS suplementado com 5,0μM de AIB.…”
Section: Resultsunclassified
“…It is considered to be the easiest method to apply, the most suitable for ensuring the genetic stability of the regenerated plant, and one of the most effective methods of ex situ short-term conservation [28][29][30]. This technique has been successfully used in different species to achieve a rapid production and regeneration of trees with desired characteristics, thus achieving genetically superior traits without gene segregation.…”
Section: Proliferation By Axillary Budsmentioning
confidence: 99%